Excretion of Nitrogenous Waste Products from the Intestinal Fluid Simulator Using Super Absorbent Polymer: A New Generation Dialysis (Iranian Journal of Kidney Diseases, 2023)
Introduction. End stage kidney disease (ESKD) is a life-threatening disorder, which results from loss of function of more than 75% of renal tissue. Many treatment modalities have been attempted for this disease, but only renal transplantation, hemodialysis and peritoneal dialysis have been practically accepted. Each of these methods have certain disadvantages, therefore other treatment modalities are needed for better management of these patients. Colonic dialysis (CD) has been proposed as one of the appropriate candidate methods for the removal of electrolytes, nitrogen waste products and excess fluid, using intestinal fluid environment. Methods. Super Absorbent Polymer (SAP) were synthesized to be used in CD. The intestinal fluid was simulated in terms of concentrations of nitrogenous waste products, electrolytes, temperature and pressure. The simulated environment was treated with 1 g of synthesized polymer at 37 °C. Concentrations of urea, creatinine and uric acid were measured before and after polymer treating. Results. Intestinal fluid simulator contained 40g urea, 0.3g creatinine, and 0.25g uric acid. SAP adsorbed up to 4000 to 4400% of its weight in the intestinal fluid simulator (1g polymer can absorb 40g fluid). The amount of urea, creatinine and uric acid decreased to 25g, 0.16g and 0.1g, respectively, in the intestinal fluid simulator. Conclusion. The present study showed that CD is an appropriate method for removal of electrolytes, nitrogenous waste products and excess fluid from an intestinal fluid simulator. Creatinine is absorbed appropriately in SAP, as a neutral molecule. In contrast, urea and uric acid, as weak acids, are absorbed weakly in polymer network.  DOI: 10.52547/ijkd.6965